Mobile App NGO One Heart Team - Mohammad Hafizul Zulkarnain; Othman, Muhaini (Applied Information Technology And Computer Science, 2023)
A mobile application is software built for small devices to enhance human interaction with the software, enabling faster and more efficient usage. The main objective of this project is to develop a mobile application for an organization called One Heart Team. This organization is a non-government organization (NGO) dedicated to helping impoverished individuals, and they aim to improve the structure of their management system. They require an application that will assist them in effectively organizing the distribution of donations to impoverished individuals. The chosen methodology for development is an object-oriented approach, and the model employed will be prototyping, allowing for recycling and improvements as needed. This mobile application will facilitate the tracking of both old and new data, enabling effective organization and management of the organization.